ANT 2004/05: AWI airborne Radio-Echo Sounding Data over western DML, south of Heimefrontfjella and over the upstream region of Slessor Ice Stream, East Antarctica (EPICA and VISA projects) - Heinrich Miller; Wilfried Jokat; Daniel Steinhage; Veit Helm (PANGAEA, 2025)
This dataset contains airborne radar data acquired using the AWI EMR system during the Antarctic season of 2004/05. The profiles extend across the western Dronning Maud Land south of Heimefrontfjella and over the upstream region of Slessor Ice Stream. The data are available as netCDF files (including waveforms and metadata), KML files of the profile line locations, and quicklook images of the radargrams.